Student-centred Teaching in Initial Teacher Education - O'Toole, Leah (Infonomics Society, 2015)
The student-centred approach to teaching advocated by Carl Rogers and others maintains that significant learning is most effectively promoted through facilitation of self-initiated, responsible action. Rogers describes his approach to teaching Psychology at university level with no prepared agenda, but rather beginning each class by asking “What would you like to learn about today?” According to Rogers the structure and organisation of self becomes more rigid under threat, and relaxes its boundaries when free from threat. Educational situations conducive to learning, therefore, ensure that ‘threat’ is reduced to a minimum. Thus, the role of a student-centred teacher is to create the kind of atmosphere in which students have the ‘freedom to learn’ and all learning, it is hypothesised, takes place in the context of ‘the relationship’ between student and teacher. This paper explores the tensions inherent in attempting to implement a student-centred approach in the current era of ‘modularisation’, ‘learning outcomes’ and ‘accountability’ in Initial Teacher Education in Ireland. The innovative approaches described were developed in teaching undergraduate student teachers in Marino Institute of Education, Dublin, Ireland. They include self-directed learning through student choice of topics; use of technology such as Twitter and Moodle, both in-class and beyond, to facilitate freedom of expression and engagement, smaller class sizes to support individualised approaches, and a focus on ‘the relationship’ between lecturer and students as a key element of the learning environment. Analysis of student feedback through qualitative, semi-structured questionnaires indicates that student-centred approaches still represent powerful pedagogical methodologies, even in the context of a contemporary neo-liberal educational climate.
Keywords: initial teacher education; student-centred teaching; Education